Activate children's intelligence using some technical activities (Journal of the College of Basic Education, 2023)
The current research aims to identify the impact of artistic activities in activating the intelligence of female children.At the age of (16) years.The experimental design of one group, with two tests, was used in the current study.pre and post.The number of the sample in the current study was (15) female students from the fourth grade of preparatory school.choose them randomly.The Otis Lyon mental ability test was used as a research tool, which aims to obtainAn accurate and comprehensive assessment of the general mental ability of secondary school students.on measuring the ease of abstract inference through the individual's response to the test items, whichIts content includes words, symbols, and shapes, and it represents a wide range of mental operations.The results showed that there were statistically significant differences at the level of significance (0.5%), in favor ofThe post-test.The study concluded that artistic activities have an effective impact on activating the students' intelligence.